Reputational crisis at a Chilean University, resulting from a post on social media X (Twitter) about the controversial theses in the School of Philosophy and Humanities - Amigo-López, Thierry; Rojas-Gomez, Diana (Frontiers in Education, 2024)
Due to the prominence of social networks since the second decade of the twenty-first century, online reputation has become essential for Higher Education Institutions (HEIs). The University of Chile, a public institution, faced a reputational communication crisis at the end of 2022 due to the disclosure on X (formerly Twitter) of two theses that relativized the concept of pedophilia. This situation raised questions about ethical integrity and permissiveness in academic research at the HEI. The research employed a qualitative methodological approach, complemented by descriptive quantitative data. The study unfolded in two distinct phases. Initially, a comprehensive review of comments on X related to the controversy was conducted. Subsequently, the comments were systematically compiled and organized in a table, and the content was downloaded from the Export Comments platform. From a pool of 4,680 messages, a representative sample of 500 comments was selected. In the second phase, the comments were meticulously categorized using the qualitative analysis tool Atlas.ti23, providing a robust and systematic approach to the research. The results showed high disapproval by X users regarding the content of the theses and the university's communication management. However, this did not directly alter the institutional reputation of the university, although it did influence the external public's perception of the professors and the organization's internal environment. The research concludes that the comments in X revealed a scarce presence of protocols on the part of the university for evaluating academic projects in the humanities.